A Systematic Approach to Define Digital Well-Being at Work - Bij de Vaate, Nadia; de Vries, Dian; Bouwmans, Machiel (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
The advancements of digital technologies continuously reshape how, where, and when employees work. While such digitalization can bring benefits for employees, it may also impose a significant burden on employee well-being. Research on how digitalization in the workplace impacts employee well-being is highly fragmented due to the myriad of digital technologies studied, as well as the vast number of well-being indicators examined. The wide variety of conceptualizations and operationalizations for both digitalization and well-being indicators hinders the ability to draw concrete conclusions. With the rapid development of novel technologies, it is crucial to find consensus about what digital well-being at work entails. The aim of this review is to unravel the existing academic landscape on employees' digital well-being and work towards an overarching framework of employee digital well-being.